2015
DOI: 10.1007/s00261-015-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of spectral CT in diagnosis of negative gallstones and common bile duct stones

Abstract: Spectral CT has a high diagnostic value for negative gallstones or bile duct stones, and material decomposition CT images and spectral curves can make an accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Spectral CT scaning can simultaneously yield mixed energy and monochromatic-energy images (40–140 keV) [ 10 , 11 , 12 , 13 ]. In general, the low energy levels with high contrast and high noise.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral CT scaning can simultaneously yield mixed energy and monochromatic-energy images (40–140 keV) [ 10 , 11 , 12 , 13 ]. In general, the low energy levels with high contrast and high noise.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that each of the selected drugs had different X-ray absorption, thus facilitating their assessment in the gastrointestinal tract. These differences result in differences in image densities, which, in addition to their size and shape, should allow the differentiation of medicines from other potential foreign bodies in the gastrointestinal tract, e.g., stones [12][13][14] and bezoars [15][16][17][18]. The pills could easily be measured on abdominal CT images and could be compared with the attenuation and noise of typical medications, as listed in table 1, to narrow down the possible identity of the agent.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy CT with virtual monoenergetic image analysis has been demonstrated to be helpful in the detection of noncalcified gallstones in the gallbladder, as discussed earlier in the "Biliary System" section (40,45). Similarly, use of virtual monoenergetic images can increase the conspicuity of isoattenuating cholesterol stones within the cystic duct or the common bile duct, which demonstrate higher and lower attenuation values compared with the surrounding bile at high and low keV values, respectively (40,41).…”
Section: Pancreasmentioning
confidence: 95%
“…Although energy-specific monoenergetic reconstruction algorithms have shown promise in the detection of gallstones isoattenuating to bile-with noncalcified gallstones having an attenuation lower than that of bile on images obtained with low-keV reconstruction (40 keV) and higher than that of bile on images obtained with high-keV reconstruction (≥140 keV) (39,40)-the sensitivity and specificity of these reconstruction algorithms have yet to be determined. Alternatively, material decomposition techniques with a calcium base, lipid base, or a calcium, lipid, and water base algorithm (three-material decomposition) provide excellent values for sensitivity and specificity, ranging from 80% to 95% and from 95% to 100%, respectively (41). The three-material decomposition technique is used routinely at our institution (Figs 12, 13).…”
Section: Biliary Systemmentioning
confidence: 99%